Crosstalk Mechanisms Between HGF/c-Met Axis and ncRNAs in Malignancy - Liu, Xin; Sun, Ranran; Chen, Jianan; Liu, Liwen; Cui, Xichun; Shen, Shen; Cui, Guangying; Ren, Zhigang; Yu, Zujiang (Frontiers in Cell and Developmental Biology, 2020)
Several lines of evidence have confirmed the magnitude of crosstalk between HGF/c-Met axis (hepatocyte growth factor and its high-affinity receptor c-mesenchymal-epithelial transition factor) and non-coding RNAs (ncRNAs) in tumorigenesis. Through activating canonical or non-canonical signaling pathways, the HGF/c-Met axis mediates a range of oncogenic processes such as cell proliferation, invasion, apoptosis, and angiogenesis and is increasingly becoming a promising target for cancer therapy. Meanwhile, ncRNAs are a cluster of functional RNA molecules that perform their biological roles at the RNA level and are essential regulators of gene expression. The expression of ncRNAs is cell/tissue/tumor-specific, which makes them excellent candidates for cancer research. Many studies have revealed that ncRNAs play a crucial role in cancer initiation and progression by regulating different downstream genes or signal transduction pathways, including HGF/c-Met axis. In this review, we discuss the regulatory association between ncRNAs and the HGF/c-Met axis by providing a comprehensive understanding of their potential mechanism and roles in cancer development. These findings could reveal their possible clinical applications as biomarkers for therapeutic interventions.